2015
DOI: 10.1007/978-94-017-9398-8_2
|View full text |Cite
|
Sign up to set email alerts
|

Morphospaces and Databases: Diatom Diversification through Time

Abstract: The diversity of diatom form inspired Art Nouveau designers, an interest renewed by recent advances in biomimetic design. The fossil record provides two windows on the diversification history of diatoms: taxonomic diversity and morphological disparity. Marine planktonic diatom diversity is conventionally interpreted to describe a steep, almost monotonic rise through Cenozoic time. Subsampling methods used to address the associated rise in sampling reveal a more stationary pattern, with peak diversity in the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…The Neogene diversification of diatoms has been linked to high latitude cooling, the evolution of the Southern Ocean and development of the cold ocean interior (Berger, 2007; Bown, 2005; Cervato & Burckle, 2003). Hypotheses linking ocean cooling to stronger oceanic fronts, increased turbulence and enhanced nutrient availability in the photic zone likely underpin (regional) increases in diatom productivity (Falkowski et al., 2005; Katz et al., 2005; Kemp et al., 1995) However, it has also been suggested that the diversity patterns are partly a sampling artifact of the “pull of the recent” and the greater sampling of more recent sediment cores (Kotrc & Knoll, 2015; Rabowsky & Sorhannus, 2009). The most up‐to‐date syntheses of morphological, genetic, and fossil data (Lazarus et al., 2014; Nakov et al., 2018) indicate that speciation rates have indeed exceeded extinction rates since the early Miocene leading to significant diversification.…”
Section: Marine Biota and Ecosystemsmentioning
confidence: 99%
“…The Neogene diversification of diatoms has been linked to high latitude cooling, the evolution of the Southern Ocean and development of the cold ocean interior (Berger, 2007; Bown, 2005; Cervato & Burckle, 2003). Hypotheses linking ocean cooling to stronger oceanic fronts, increased turbulence and enhanced nutrient availability in the photic zone likely underpin (regional) increases in diatom productivity (Falkowski et al., 2005; Katz et al., 2005; Kemp et al., 1995) However, it has also been suggested that the diversity patterns are partly a sampling artifact of the “pull of the recent” and the greater sampling of more recent sediment cores (Kotrc & Knoll, 2015; Rabowsky & Sorhannus, 2009). The most up‐to‐date syntheses of morphological, genetic, and fossil data (Lazarus et al., 2014; Nakov et al., 2018) indicate that speciation rates have indeed exceeded extinction rates since the early Miocene leading to significant diversification.…”
Section: Marine Biota and Ecosystemsmentioning
confidence: 99%